Thai Radical Discourse : The Real Face of Thai Feudalism Today - Reynolds, Craig J. (Book collections on Project MUSE., 1987)
Using Jit Poumisak's The Real Face of Thai Feudalism Today (1957), Reynolds both rewrites Thai history and critiques relevant historiography. Discussing imperialism, feudalism, and the nature of power, Reynolds argues that comparisons between European and Thai premodern societies reveal Thai social formations to be "historical, contingent, and temporally bounded."